ALAT CEKAT FUNGSIONAL JASPER JUMPER DALAM BIDANG ORTODONTI - Retno Widayati; Erwin Siregar (Faculty of Dentistry, Universitas Indonesia, 2015)
Jasper Jumper is an orthodontic appliance that belongs to fixed functional appliance. This appliance is designed to correct class II malocclusion case, and also further development of Herbst's. Jasper Jumper can be used to move a tooth, a group of teeth, or the entire denture. In addition, this appliance can produce the same effect as headgear, activator, or any combination of them. Understanding of selected cases, biomechanics and the working mechanism of Jasper Jumper is very helpful for operators working with this appliance in clinics.